Influence of obesity in interstitial lung disease associated with anti-aminoacyl-tRNA synthetase antibodies. (March 2022) - Yamaguchi, Koichi; Fukushima, Yasuhiro; Yamaguchi, Aya; Itai, Miki; Shin, Yuki; Uno, Shogo; Muto, Sohei; Kouno, Shunichi; Tsurumaki, Hiroaki; Yatomi, Masakiyo; Aoki-Saito, Haruka; Hara, Kenichiro; et al.
Abstract: Background: Obesity is a major risk factor for developing various respiratory diseases. Patients with anti -aminoacyl tRNA synthetase (ARS) antibodies often have interstitial lung disease (ILD). The present study was conducted to evaluate the association between obesity and outcomes of anti-ARS antibody-related ILD (ARS-ILD). Methods: We retrospectively investigated 58 patients with ARS-ILD and compared the clinical characteristics, treatment, and prognoses between obese (body mass index [BMI] ≥25 kg/m 2 ) and nonobese (BMI <25 kg/m 2 ) patients. Chest fat was quantified via computed tomography (CT). Thoracic subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) were measured at diagnosis and first relapse of ILD. Results: Sixteen patients were obese. Obese patients had lower percentages of predicted diffusing capacity of the lungs for carbon monoxide and higher high-resolution CT scores and SAT and VAT indexes than did nonobese patients. The ILD relapse rate was higher in obese patients ( P  < 0.01), especially among those with high SAT indexes ( P < 0.01). The SAT and VAT indexes increased significantly from diagnosis until first relapse. Among clinical parameters at first relapse, SAT and VAT indexes were correlated with serum Krebs von den Lungen‐6 levels (r = 0.720, P = 0.008) and total ground-glass attenuation scores (r = 0.620, P = 0.024), respectively. Conclusions: Obesity and high SAT indexes are risk factors for ILD relapse in patients positive for anti-ARS antibodies. Evaluating and quantifying patients' chest fat on CT is important for predicting ILD relapse. Highlights: Obese patients positive for anti-ARS antibodies have high relapse rates of ILD. Chest fat quantification of SAT and VAT is associated with activity of ILD. Thoracic SAT index is a risk factor for ILD.